GROUP DISCUSSION AS A METHOD OF INSTRUCTION - Nur Aflah, Mita (Jurnal Ilmiah Spectral, 2017)
This paper sets out to explore the theory on classroom instruction particularly group discussion. It includes a short discussion of thebenefits of group discussion as an activity to help engaging students in a lesson by encouraging spoken interactions. It alsoprovides a guided discussion to apply in the classroom as the subject matter for students to learn to discuss more effectively. Hopefully the paper could provide educators and instructors a method to use and to lead further studies for helping students to increase their opportunities to have authentic communication in English. Moreover, this paper can also serve as a research reference in the field of classroom instruction, for instance in using group discussion to develop speaking skill.